Fervent and open. - Heim, S. Mark (Christian Century, 2013)
A review of the book "Why Did Jesus, Moses, the Buddha, and Mohammed Cross the Road? Christian Identity in a Multi-Faith World," by Brian D. McLaren, is presented.